Types and cost of wellness services provided by a neighborhood-based academic nursing center - Han, Hae-Ra; Lee, Yoon-Jae; Lee, Jennifer J.; Sun, Chun-An; Dapaah-Gyimah, Ophelia; Wilson, Patty; Ling, Catherine; Slade, Eric (Frontiers in Public Health, 2025)
BackgroundDespite increased insurance coverage since 2010, racial and ethnic minorities in the United States still receive less medical care than White counterparts. The Johns Hopkins School of Nursing’s Center for Community Programs, Innovation, and Scholarship (COMPASS Center) provides free wellness services, aiming to address healthcare disparities in the neighborhoods.ObjectiveTo delineate the types and cost of wellness services provided by the COMPASS Center.MethodsThe study employed a secondary analysis design, utilizing Qualtrics surveys to assess wellness service data from 2017 to 2022 at two main program sites—Wald center and House of Ruth, Maryland.ResultsThe analysis covered 2,194 encounters (826 at Wald center and 1,368 at House of Ruth, Maryland). Most encounters at both sites served African American/African/Black and low-income individuals. Examples of wellness services included pre-employment exams and immunizations, health literacy and self-care management education, health insurance advice, parenting support, and referrals to community resources. Cost analysis revealed varying expenses per encounter, with medium costs ranging from 5.45 to 14.91 across sites, considering service type and duration, including staff salaries, encounter numbers, and service hours.ConclusionThe COMPASS Center delivers essential wellness services supplementing traditional healthcare to disadvantaged community members through student engagement and academic support. The next generation of healthcare teams is learning with and from the community creating a holistic educational experience in building skills outside of institutional bedsides. Future plans involve structured training for students and center staff to provide wellness services, while expanding social service referrals. More work is needed to evaluate the impact of our wellness services on client satisfaction and wellness improvements.